Lymphoplasmacytic Plaque in Children: A Demonstrative Case of an Emerging Clinicopathologic Entity. Issue 6 (30th August 2016) - Porto, Dennis A.; Powers, Molly; Patel, Devika; Chaffins, Marsha; Shwayder, Tor A.
Abstract: Lymphoplasmacytic plaque in children is a rare but increasingly reported clinicopathologic entity characterized by extratruncal erythematous solitary plaques, most often in children and Caucasian girls, that are thought to be a reactive or pseudolymphomatous process. We report a demonstrative case of lymphoplasmacytic plaque in a 3‐year‐old girl and discuss the clinical and pathologic experience with this entity.